Stereotypes and emotions: the middle class in the argentine popular press around the twenties - Mannocchi, Cintia Mariela (Revista de Historia Social y de las Mentalidades, 2025)
This article will study the way in which the category “middle class” was extended in the Argentine popular press at the end of the 1910s and beginning of the 1920s. Emphasis will be placed on the relationships between the construction of class identity, the emotions that circulated in the discourses and the social stereotypes that were related to these emotions. Our methodology used, on the one hand, the discursive analysis of articles and reports from popular newspapers and magazines; on the other hand, union magazines, militant magazines, specialized magazines, plays and massive novels to compare and link. The hypothesis to be worked on consists of importance that emotions associated with stereotypical images had in the formation of an early middle class identity.